FINANCIAL MANAGEMENT AND ASSETS IN INCREASING REAL REGIONAL INCOME (PAD) - *, Supardi; Bonaventura Ngw, Prof. Dr.; Si, M.; Jatmikowati, Dr. Sri Hartati; Si, M. (IJRDO - Journal of Business Management, 2017)
The era of regional autonomy as well as the organization of the boarding costs increase government bureaucracy needed for local government able to implement the strategic plan development accordance with region. To review the effectiveness of the organization as well as the analysis of relevant being studied mainly the department of revenue, finance and asset management as the one responsible institutions against extracting revenue. Singer study aims to review the effectiveness of the organization and determine rate, and factors affecting the level of achievement of the effectiveness of the department of revenue, finance and asset management.Research singer included operates qualitative study, stressed on search process and disclosure, meaning behind the phenomena appears hearts research, with the aim that the issue will be examined more is comprehensive, deep, natural and what and without much mixed serbi from research to the effectiveness of the office revenue, finance and asset management managing hearts source-source original income. From the findings of the national research and analysis found that the effectiveness of the office of the department of revenue, finance and asset management operations the scalable optimal productivity levels realization of local revenue target has exceeded has set. with organizational structure education level indicator apparatus and placement already accordance with competence. Factors with cooperation unit other subscribe already runs with maximum. Also employees of administrative capacity factor pretty good. Also such factors planning work program has been running well, only variables optimal job satisfaction not caused by shifting system that is not sufficient. The recommendation of this research is to increase the effectiveness of the organization through the increase of revenue of Original Regional Revenue through intensification and extensification of all sources of Original Revenue proportionally, improvement of organizational effectiveness through improvement of Human Resources (HR) and improvement of incentive system for apparatus Dinas Revenue, Financial Management and Assets